Oral traditions in cryptic song lyrics; Continuous cultural revitalization in Batuley - Gordon, A. Ross; Djonler, Sonny A. (Wacana, Journal of the Humanities of Indonesia, 2019)
Oral knowledge and teachings are referenced but not salient in cryptic song lyrics sung at ritual festivals in Batuley villages of the Aru Islands in Eastern Indonesia. The article examines the relation of the lyrics in songs to associated teachings and how they are vitalized and transmitted over centuries with veracity. Song teachings relate to pearl oyster and sea cucumber harvests, and cosmological beliefs associated with the Maluku Siwa-Lima trade-based moiety system, which took on a unique form in the Aru Islands. Song-related teachings demonstrate cultural adaptations giving meaning to centuries of peripheral engagement in hemispheric trade networks by a geographically isolated community. The article evaluates the role of historical truth in building community and identity within a minority culture and language group.